Penerapan Innovative Entrepreneur Dalam Upaya Meningkatkan Kemandirian Pada Mahasiswa (Studi Analisis Mahasiswa Ekonomi Syariah STAINIM Sidoarjo) - Dewi Riza Lisvi Vahlevi (Program Studi Ekonomi Syariah, STAI AN-NAJAH INDONESIA MANDIRI, 2022)
Innovativepreneur is one form of uniqueness in entrepreneurship. This is because there is a lot of competition in the world of business and industry, so it demands for the book of Jesus to provide something different to be able to attract consumer interest.STAINIM, which has a campus motto, Religious Entrepreneur, must be able to produce students who are able to create their own business opportunities. This study uses a qualitative descriptive method based on the contributions of researchers as lecturers and activists, as well as with students. From this study, it was found the phenomenon of increasing the number of students' income from several products being sold, so that it could increase their confidence to be able to develop their business and could motivate other friends who are still shy to step up. Keywords : Innovativepreneur, independence Referensi Fajrillah, dkk, 2020. Smart Entrepreneurship: Peluang Bisnis Kreatif dan Inovatif di Era Digital, Medan: Yayasan Kita Menulis. Katut Sutrisna Dewi, Sayu. 2012. Konsep dan Pengembangan Kewirausahaan di Indonesia. Sleman: Deepublish. Sisca, dkk.., 2021. Manajemen Inovasi, Medan: Yayasan Kita Menulis. Suryana, 2013. Kewirausahaan : Kiat dan Proses Menuju Sukses, Jakarta: Salemba Empat.